2006
DOI: 10.1128/jvi.00162-06
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Replication in Human Macrophages Induces NF-κB-Dependent Tumor Necrosis Factor Alpha Production

Abstract: Rhinoviruses (RV) are the major cause of acute exacerbations of asthma and chronic obstructive pulmonary disease (COPD). Rhinoviruses have been shown to activate macrophages, but rhinovirus replication in macrophages has not been reported. Tumor necrosis factor alpha (TNF-␣) is implicated in the pathogenesis of acute exacerbations, but its cellular source and mechanisms of induction by virus infection are unclear. We hypothesized that rhinovirus replication in human macrophages causes activation and nuclear tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 67 publications
(98 reference statements)
5
100
2
1
Order By: Relevance
“…A small amount of viral replication has been noted in RV-infected peripheral blood monocyte-derived macrophages but not in BAL-derived macrophages (3,4). Nevertheless, in these studies, ex vivo exposure to UV-irradiated, replicationdeficient RV induced similarly robust production of TNF-a (3) and IP-10 (6).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A small amount of viral replication has been noted in RV-infected peripheral blood monocyte-derived macrophages but not in BAL-derived macrophages (3,4). Nevertheless, in these studies, ex vivo exposure to UV-irradiated, replicationdeficient RV induced similarly robust production of TNF-a (3) and IP-10 (6).…”
Section: Discussionmentioning
confidence: 64%
“…Although it has been demonstrated that macrophages allow RV entry (3,4,7,25), the ability of RV to replicate in macrophages remains controversial. BMMs were infected with RV or replication-deficient UV-RV.…”
Section: Effects Of Il-4 On Bmm Surface Markers and Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…AS602868 inhibits the activation of the IKK kinase responsible for the degradation of NF-kB inhibitors, and consequently decreases intracellular levels of NF-kB [13]. We used the IKK2 inhibitor AS602868 at a concentration previously shown to be optimal for rhinovirus-induced tumour necrosis factor-a inhibition without cell toxicity [13].…”
Section: Nf-kb Activationmentioning
confidence: 99%
“…The effect of NF-kB activation on RSV-induced IL-15 production was evaluated using an IkB kinase (IKK)2 inhibitor (AS602868) as previously described [13]. AS602868 inhibits the activation of the IKK kinase responsible for the degradation of NF-kB inhibitors, and consequently decreases intracellular levels of NF-kB [13].…”
Section: Nf-kb Activationmentioning
confidence: 99%